Factors Associated With Psychological Adjustment in Adults With Cleft Lip and/or Palate: Findings From a National Survey in the United Kingdom. (April 2022) - Costa, Bruna; Ardouin, Kenny; Stock, Nicola Marie
Objectives: Research has identified adults born with cleft lip and/or palate (CL/P) to be at risk of poorer psychological outcomes compared to the general population. This study investigated factors that may contribute to positive and negative adjustment in adults born with CL/P. Design: A survey was designed and distributed by the Cleft Lip and Palate Association in collaboration with the Centre for Appearance Research CAR at the University of the West of England (UWE). There were 207 eligible responses (95% completed online) received between July and October 2018. Dependent variables included the Body Esteem Scale for Adolescents and Adults, Harter's Self Perception Profile for Adults (Global Self-Worth, Social Competence, and Intimacy subscales), the Fear of Negative Appearance Evaluation Scale, and the Revised Adult Attachment Scale. Independent variables were the Revised Life Orientation Test, biodemographic data, and self-reported single-item questions. Results: Factors associated with positive adjustment included reports of a happy childhood, talking about CL/P with family, close friendships, comfort in public spaces, satisfaction with appearance, and a positive life orientation. Psychological distress was associated with a desire for further surgery to improve appearance and/or function. Conclusions: Several factors were identified that may influence psychological adjustment in adults with CL/P. Throughout childhood, family-centered practice to support family cohesion and an open dialogue about CL/P is indicated, as is support for young people to develop social confidence. For adults returning to the cleft service, treatment options for appearance and/or functional concerns should be explored, with access to psychological support when indicated. Interventions to increase optimism, resilience, and self-acceptance may also be warranted throughout the life span.